'Illat and Wisdom in Use Ultrasonography (USG) during Iddah Period: Comparative Study - Arafah, Muhammad; Nur, Irsan; Sofyan; Asti, Mulham Jaki; Rahmatullah, Andi Muhammad Ridha (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
The Iddah phenomenon is a contemporary issue in which the essence of the Iddah period for women experiences certain problems, including the prohibition of women during their Iddah period from accepting proposals or getting married, lack of understanding of the determination of the Iddah period, gender inequality issues, and conflicting understandings of law and calculation of the Iddah period. Consequently, the use of ultrasound during the Iddah period has become a topic of discussion. This article discusses the contextualization of Islamic law that seeks to place illat and wisdom at the center of cases involving the use of ultrasound during the Iddah period to determine the cleanliness of a woman's uterus, so that the existence of illat becomes the basis for legal istinbat, which then gives birth to wisdom. The research method employed is qualitative with literature review, which attempts to establish a connection between the relevant literature and the article's discussion. This study's findings identify the use of ultrasound during the Iddah period as a criterion for the existence of illat and the wisdom that underlies its legal determination. Therefore, the existence of ultrasonography (USG) during the Iddah period based on a theological approach cannot be used as a benchmark (illat) for uterine hygiene for women and does not affect the essence of the wisdom contained therein, including for matters that are clear and certain that are used to establish and determine whether or not a law exists.